Dampak Rehabilitasi Jaringan Irigasi Perdesaan terhadap Adopsi Teknologi Budi Daya Padi - Zakaria, Amar K. (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
The rehabilitation of irrigation canal on the rural area is very important to rice farmers because the use of water is becoming more eficient and rice production and farmer’s income is increasing. Increasing the rice productivity would be considered as an indication of farmer’s participation on the adoption of technology. The present study was aimed to evaluate the technology adoption on rice farming in relation with the irrigation canal rehabilitation. The study was carried out in Majalengka district of West Java, during 2012 using survey method. The data were collected through the interview techniques to 44 farmer respondents using structured questionnaires. The data were cross tabulated and to measure the advantage of adopting the technology, Gross R/C ratio was calculated along with the break even point/BEP. Result of the analyses showed that after rehabilitation of the rural irrigation infrastructure the water supply was becoming more available and farmers were motivated to adopt the rice farming technology and the management of rice cultivation. The degree of technology adoption was considered as optimum and economically was feasible, as indicated by the value of R/C between 1.98 and 2.15, with the profitability of 49.6 percent to 53.5 percent. The partial budgetting analysis showed the B/C marginal of 2.59 and growing Ciherang rice variety is considered to be profitable.